PENGELOLAAN KURIKULUM DAN PEMBELAJARAN DI SEKOLAH DASAR BERBASIS PESANTREN - Anggara Dwinata; Ngainun Naim (An-Nahdliyyah: Jurnal Studi Keislaman, 2023)
This study discusses curriculum development in schools and Islamic boarding schools. The objectives are (1) to find out the basis for implementing Islamic boarding school-based curriculum and learning, (2) to find out the factors that support and activate the implementation of Islamic boarding school-based curriculum and learning. The method used in this research is a qualitative approach with a case study research design. Data collection techniques with the process of observation, interviews, and documentation. The results of the study prove that: (1) SD Plus Pesantren Al-Anwar uses a curriculum that has been instructed by the local education office and Islamic boarding school, (2) learning is carried out according to formal school hours and learning is also carried out while students live in dormitories. The supporting factors are the existence of appropriate school policies, professional teachers, and complete infrastructure. While the inhibiting factors include the condition of students or students who are less responsible in terms of learning, so they seem to still like to play and learn less optimally.